Openness As A Pathway To Support Sdgs : An Exploration Of Science-Society Mediation Spaces - Mboa Nkoudou, Thomas Hervé (My University, 2020)
Here are slides and the full text of my plenary talk during the Citizen Science Conference 2020.Knowledge for Change: A decade of Citizen Science (2020-2030) in support of the SDGs (Berlin, 14.-15. October 2020).
Keywords: decolonial thinking; SDG; Citizen science